prove that. (2x-3y)^3+(3y-4z)^3+(4z-2x)^3=3(2x-3y)(3y-4z)(4z-2x)
Answers
Answered by
1
Answer:
(2x−3y)
3
+(3y−4z)
3
+(4z−2x)
3
The equation can be written in this way
We know, (a)
3
+(b)
3
+(c)
3
−3abc=(a+b+c)(a
2
+b
2
+c
2
−ab−bc−ca)
if a+b+c=0, then (a)
3
+(b)
3
+(c)
3
=3abc
Hence as we see, 2x−3y+3y−4z+4z−2x=0
(2x−3y)
3
+(3y−4z)
3
+(4z−2x)
3
=6(2x−3y)(3y−4z)(2z−x)
Similar questions
Social Sciences,
3 months ago
Math,
3 months ago
Physics,
3 months ago
India Languages,
6 months ago
Math,
6 months ago
Math,
1 year ago
Physics,
1 year ago